2007
DOI: 10.1162/qjec.122.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Does Head Start Improve Children's Life Chances? Evidence from a Regression Discontinuity Design

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
607
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 809 publications
(643 citation statements)
references
References 33 publications
11
607
3
3
Order By: Relevance
“…In 2SLS b the first-stage model include as predictors the number of school-age years of exposure to school finance reform interacted with the median districtpredicted reform-induced change in school spending in the state. 1972-2010Annually 1987-2010Annually 1987-20101987, 1990, 1993, 1999, 2007 Previous historical data on per pupil expenditures was only available in a readily usable format via the Census of Governments: School System Finance (F-33) File (U.S. Bureau of the Census, Department of Commerce). The Census of Governments previously was only conducted in years that end in a two or seven, so at the time when many important papers on SFRs were written, there were many years of missing data.…”
Section: Effect Of Court-mandated Reforms On Spending and Outcomes: Imentioning
confidence: 99%
See 1 more Smart Citation
“…In 2SLS b the first-stage model include as predictors the number of school-age years of exposure to school finance reform interacted with the median districtpredicted reform-induced change in school spending in the state. 1972-2010Annually 1987-2010Annually 1987-20101987, 1990, 1993, 1999, 2007 Previous historical data on per pupil expenditures was only available in a readily usable format via the Census of Governments: School System Finance (F-33) File (U.S. Bureau of the Census, Department of Commerce). The Census of Governments previously was only conducted in years that end in a two or seven, so at the time when many important papers on SFRs were written, there were many years of missing data.…”
Section: Effect Of Court-mandated Reforms On Spending and Outcomes: Imentioning
confidence: 99%
“…1 undetected by test scores (e.g. Heckman, Pinto, & Savelyev, 2014;Deming 2009;Jackson, 2012;Chetty, Friedman and Rockoff, 2013;Ludwig and Miller, 2007). We address the limitations of focusing on test scores as our main outcome by focusing on the effect of school spending on longrun outcomes such as educational attainment and earnings.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-kindergarten programs have been evaluated using RCTs (Campbell et al, 2014;Muennig et al, 2011a,b;Muennig et al, 2009), at least one regression discontinuity analysis (Ludwig and Miller, 2007), and case-control studies (Palfrey et al, 2005;Reynolds et al, 2001). These all show an impact on behavioral risk factors for health or actual measures of health.…”
Section: Pre-kindergarten Programs and Healthmentioning
confidence: 99%
“…However, a regression discontinuity study of the broader Head Start program (unrelated to the above mentioned RCT) showed reductions in mortality for children aged 5 to 9 (Ludwig and Miller, 2007). These reductions in childhood mortality were thought to arise from the funding and technical assistance provided by the Office of Economic Opportunity in 1965 to develop Head Start programs.…”
Section: Head Startmentioning
confidence: 99%
“…This acknowledgement has been based on research that has been conducted in the developed world (Barnett & Masse, 2007;Camilli, Vargas, Ryan, & Barnett, 2010;Ludwig & Miller, 2007) and in East Africa (Malmberg, Mwaura, & Sylva, 2011). In response to this trend, some African governments have tried to adapt best practices from the western world that follow normative western ideologies about child development (Pence & HixSmall, 2009).…”
Section: Introductionmentioning
confidence: 99%